Trading on target : how to cultivate a winner's state of mind - Toghraie, Adrienne Laris (Hoboken, N.J. : Wiley, 2011)
'Trading on Target explains the rites of passages that traders pass through in order to develop a high level of mastery. Most aspiring traders stumble or become discouraged at some point in the process. Most don't have a good overview of what success requires and, as result, are unprepared for the challenges. Author and trading coach Adrienne Toghraie identifies the rites of passages, as follows: raising adequate capital; developing market knowledge; developing a trading system; testing the system; managing the business of trading; managing the psychological pitfalls of trading; surviving market losses; surviving market change; and developing an intuitive sense of the markets. Toghraie discusses the rites of passage in the context of real traders she has counseled, and, in so doing, reveals the myriad of obstacles that prevent traders from succeeding. Many traders attempt to take shortcuts and don't do the requisite work; some are addicted to risk-taking; some fail to take responsibility for their own success and blame outside agencies for their problems. Toghraie provides insights into how traders overcame these problems achieved higher levels of performance. She explains how principles of neuro-linguistic programming can be used by traders to manage their mental states for optimal performance. Geared primarily for independent traders, the book provides a realistic and helpful overview of what it takes to succeed in trading'--
Includes index.
Keywords: Investment analysis; Investments; Success in business